GE_GERICHTE C/3364/2017 vom 19. Juni 2018 - GE Cour de justice (2018)
DIVORCE ; MESURE PROVISIONNELLE ; OBLIGATION D'ENTRETIEN ; ENFANT ; MINORITÉ(ÂGE) ; REVENU HYPOTHÉTIQUE | CC.179.al1; CC.276; CC.286